If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -12 + 4x + -1 = -1x + -7 + 12 + -3x + 5 Reorder the terms: -12 + -1 + 6x + 4x = -1x + -7 + 12 + -3x + 5 Combine like terms: -12 + -1 = -13 -13 + 6x + 4x = -1x + -7 + 12 + -3x + 5 Combine like terms: 6x + 4x = 10x -13 + 10x = -1x + -7 + 12 + -3x + 5 Reorder the terms: -13 + 10x = -7 + 12 + 5 + -1x + -3x Combine like terms: -7 + 12 = 5 -13 + 10x = 5 + 5 + -1x + -3x Combine like terms: 5 + 5 = 10 -13 + 10x = 10 + -1x + -3x Combine like terms: -1x + -3x = -4x -13 + 10x = 10 + -4x Solving -13 + 10x = 10 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -13 + 10x + 4x = 10 + -4x + 4x Combine like terms: 10x + 4x = 14x -13 + 14x = 10 + -4x + 4x Combine like terms: -4x + 4x = 0 -13 + 14x = 10 + 0 -13 + 14x = 10 Add '13' to each side of the equation. -13 + 13 + 14x = 10 + 13 Combine like terms: -13 + 13 = 0 0 + 14x = 10 + 13 14x = 10 + 13 Combine like terms: 10 + 13 = 23 14x = 23 Divide each side by '14'. x = 1.642857143 Simplifying x = 1.642857143
| 0=n^2+200 | | -5n+4=5n+34 | | 2x-26=x+3 | | 8(4x-12)=8x-18 | | 9f+7=-8f+24 | | 2x-29=x+2 | | 2x-10=5x+9 | | 0=n^2+60n+1600 | | 2x-27=x+2 | | 8(x+2)=3(x-5)-7(x+3) | | 5p+7+14p+40= | | 3q=3q-3 | | 0=n*2+60n+1600 | | 2x-27+x+2= | | .19-5m=34 | | .75m+3=-12 | | (2x-27)+(x+2)= | | 2.4=-8(.3p+9) | | 6x+13=-51-10x | | 4(x+3)-2(-x+3)=6-x | | y=x^2-6x+10 | | 4(2h+3)=6 | | 16=.33t+8 | | 8b+2=34 | | 9w+3=39 | | .2x+4=9 | | 4x+2+36x+8= | | 5t^2-26tx+5x^2=0 | | 4x+9=-51 | | .333n+6=9 | | 11x-16=72 | | 0.4a=5 |